Zinc Oxide Tetrapods Doped with Silver Nanoparticles as a Promising Substrate for the Detection of Biomolecules via Surface-Enhanced Raman Spectroscopy - Vanags, Edgarss; Bite, Ivita; Ignatane, Liga; Ignatans, Reinis; Trausa, Annamarija; Tipaldi, Ciro Federiko; Vilks, Karlis; Smits, Krisjanis (MDPI, 2024)
In this study, we report the fabrication and characterization of silver nanoparticle-doped zinc oxide tetrapod substrates used for surface-enhanced Raman scattering to detect rhodamine B. Prior to this, silver nanoparticle-doped zinc oxide tetrapods were synthesized using the solar physical vapor deposition method. Subsequently, silver-doped zinc oxide tetrapods were applied onto silicon wafers via the droplet evaporation process. The surface-enhanced Raman scattering activity of the silver nanoparticle-doped zinc oxide tetrapod substrate was evaluated by detecting rhodamine B using Raman spectroscopy. Our results demonstrate that the silver nanoparticle-doped zinc oxide tetrapod substrate exhibits surface-enhanced Raman scattering activity and can detect rhodamine B at concentrations as low as 3 μg/mL. This study suggests that silver nanoparticle-doped zinc oxide tetrapod substrates have potential as surface-enhanced Raman scattering platforms as well as potential for the detection of biomolecules. © 2024 by the authors. This is an open-access article: Vanags, E.; Bite, I.; Ignatane, L.; Ignatans, R.; Trausa, A.; Tipaldi, C.F.; Vilks, K.; Smits, K. Zinc Oxide Tetrapods Doped with Silver Nanoparticles as a Promising Substrate for the Detection of Biomolecules via Surface-Enhanced Raman Spectroscopy. ChemEngineering 2024, 8, 19; https://doi.org/10.3390/chemengineering8010019 published under the CC BY 4.0 licence.
This research was funded by European Regional Development Fund project Nr. 1.1.1.1/21/A/053 realized at the Institute of Solid State Physics, University of Latvia. The Institute of Solid State Physics, University of Latvia, as the Center of Excellence, received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; rhodamine B detection; SERS; silver nanoparticles; tetrapods; ZnO